Hospital-Based Study on Gastrointestinal Impaction Disorders in Dairy Buffaloes - YADAV, ANNU; Kumar, Ankit; Kumar, Tarun; Sharma, Maneesh; Punia, Sunil; Sangwan, Mukesh; Sindhu, Neelesh (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Gastrointestinal impaction is mainly encountered during months of feed scarcity.  Present study was aimed to throw light on the clinical characteristics of gastrointestinal impaction in 103 dairy buffaloes out of 1036 brought to VCC, LUVAS, Hisar, Haryana for various ailments and its associated haemato-biochemical alterations during March 2022 to June 2022. Overall hospital-based prevalence of gastrointestinal impaction was found to be 9.94 % (103/1036), being significantly higher in May month in comparison to other three months. Majority (70.8%) animals were anorectic and had rumen stasis, hard rumen texture. Haematological picture depicted significant neutrophilia and lymphopenia with non-significant variation in other parameters. Biochemical analysis revealed hypocalcemia, hyperglycemia, hyponatremia, hypochloremia, hypophosphatemia, hypokalemia and increased BUN with non-significant variation in total protein and creatinine. Standard treatment either surgical or non-surgical was based on clinical and haemato-biochemical variations. The dairy buffaloes are prone to gastrointestinal impaction on wheat and paddy straw feeding although the gradual introduction of new fodder with supplementation of minerals and electrolytes along with proper treatment of fresh wheat straw should be adopted for prevention.
Keywords: Buffaloes; Foreign body syndrome; Hypocalcemia; Hypokalemia; Impaction